2015
DOI: 10.1002/macp.201500171
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Formation of ZnO‐graft‐Poly(d,l‐Lactide) Hybrid Systems via Microwave‐Assisted Polymerization of d,l‐Lactide in the Presence of ZnO Nanoparticles

Abstract: The surface modification of inorganic nanoparticles by polymer grafting is generally required for obtaining well dispersed polymer‐based (bio)nanocomposites, and the in situ polymerization of corresponding monomers is considered to be a versatile approach to this purpose. In this work, the microwave‐assisted ring‐opening polymerization of d,l‐lactide in the presence of zinc oxide (ZnO) nanoparticles affords an original and straightforward method for generating ZnO‐graft‐poly(d,l‐lactide) hybrid systems. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Regarding the composite coaxial ABS/PAN-ZnO fibers, it was observed that the higher the ZnO content, the lower the contact angle, probably due to the hydroxyl groups on the ZnO particles surface. 49,50 Considering the polarity, ABS/PAN-ZnO nanofibrous materials can be envisioned as suitable membranes for water purification.…”
Section: Abs/pan Materials Engineered By Coaxial Electrospinningmentioning
confidence: 99%
“…Regarding the composite coaxial ABS/PAN-ZnO fibers, it was observed that the higher the ZnO content, the lower the contact angle, probably due to the hydroxyl groups on the ZnO particles surface. 49,50 Considering the polarity, ABS/PAN-ZnO nanofibrous materials can be envisioned as suitable membranes for water purification.…”
Section: Abs/pan Materials Engineered By Coaxial Electrospinningmentioning
confidence: 99%
“…The acceleration effect arising from multi-modal microwave irradiation could initially be attributed to the formation of a greater amount of zinc lactate (during the freeze-drying stage) prone to form the initiating species of LA polymerization, as previously reported by several authors. [8,[9][10][11] However, the FTIR spectrum of the freeze-dried reaction mixture for multi-modal microwave irradiation did not evidence the presence of one such zinc compound (Figure 2c), i.e. after freeze-drying the mixture consisted of only D,L-lactide and ZnO nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Rodríguez‐Tobías et al . have carried out the microwave‐assisted ROP of D,L ‐lactide in the presence of ZnO micro‐ and nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such modified NPs can be easily homogeneously dispersed and distributed in a polymer matrix to produce a functional nanocomposite [15]. Rodríguez-Tobías et al [17] modified the surface of zinc oxide NPs (ZnO NPs) with polylactic acid (PLA), synthesized by microwaves. The authors proposed grafting mechanisms, between ZnO NPs and the PLA, establishing the existence of different reactions that explain the formation of the hybrid system (ZnO-graft-PLA).…”
Section: Introductionmentioning
confidence: 99%